1997
DOI: 10.21836/pem19970514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different postbreeding treatments on fertility of thoroughbred mares

Abstract: SummaryThe purpose of this study was to determine whether the postbreeding intrauterine treatments with homologous plasma, homologous plasma with leukocytes, or homologous plasma with antibiotics improve pregnancy rates per cycle. Control mares received no treatment. Mares (n=394) were assigned to different groups according to their reproductive status. All mares in each group were randomly allocated to one of the treatments. lntrauterine treatments were given 13 to 36 hours after mating, The early pregnancy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
1
0
0
1
Order By: Relevance
“…Data presented in this work showed that the pregnancy rate of maiden mares bred in the 1 st estrus cycle during the breeding season was significantly lower (63.7%) than that of the mares bred in other estrus cycles (80.3%), results similar to those observed previously by Mattos et al (1997 and1999). However, no significant difference (p>0.05) regarding the EL rate was observed between the first and other estrus cycles, being the EL rates in agreement with those found by Ginther (1992).…”
Section: Discussionsupporting
confidence: 91%
“…Data presented in this work showed that the pregnancy rate of maiden mares bred in the 1 st estrus cycle during the breeding season was significantly lower (63.7%) than that of the mares bred in other estrus cycles (80.3%), results similar to those observed previously by Mattos et al (1997 and1999). However, no significant difference (p>0.05) regarding the EL rate was observed between the first and other estrus cycles, being the EL rates in agreement with those found by Ginther (1992).…”
Section: Discussionsupporting
confidence: 91%
“…Hiermit ist die In-Vitro-Basis fur eine mögliche therapeutische Anwendung des Verfahrens geschaffen, die in der intrauterinen Inokulation vitaler und im mu nk o mp et e n te r , ho rn o lo g e r od e r h e ter o lo ge r PM N bei bakteriell endometritiserkrankten Stuten bestehen wird. Felduntersuchungen an suszeptiblen StLrten liegen inzwischen vor (Castilho 1994;Mattos et al 1997) . Nach der Bedeckung wurden aus dem Blut frisch separierle PMN intrauterin appliziert.…”
Section: Materials Und Methodenunclassified